Analisis Diagnostik Kesulitan Belajar Bangun Ruang pada Siswa Kelas V Sekolah Dasar: Tinjauan Konseptual, Prinsip, dan Prosedural - Putri, Windi Harisa; La Fua, Jumarddin; Halistin (IAIN Kendari, 2025)
Learning difficulties in mathematics, particularly in solid geometry, remain common in primary schools and can hinder learning mastery. This study aimed to describe the profile of fifth-grade students’ learning difficulties in solid geometry at SD Negeri 22 Kendari. A qualitative descriptive design supported by descriptive statistics was employed. Data were collected through a story-based diagnostic test, classroom observation, teacher and student interviews, and documentation. The participants consisted of 30 students, with in-depth analysis focusing on 21 students who did not meet the mastery criterion. The findings indicate that the most prominent difficulties were conceptual, including distinguishing solid figures, understanding geometric elements, and using measurement units accurately. Principle-related difficulties appeared in selecting and applying surface area and volume formulas according to problem contexts, especially when linking given information to formula variables. Procedural difficulties involved arithmetic errors, incomplete solution steps, and low computational accuracy. These results highlight the importance of diagnostic assessment and instruction that prioritizes conceptual understanding, relationships among geometric elements, and systematic problem-solving strategies to inform targeted remedial support. Keywords: mathematics learning difficulties; solid geometry; primary school; diagnostic assessment; misconceptions; problem solving